Athletic participation in the young patient with an implantable cardioverter-defibrillator. (13th January 2017) - Lampert, Rachel; Law, Ian
Abstract: The decision of whether to allow a young patient with an implantable cardioverter-defibrillator to continue to participate in sports is complex and multi-factorial. The positive physical and psychosocial impact of sports participation must be weighed against the potential adverse events associated with implantable cardioverter-defibrillators. Arrhythmias appear to be more prevalent in athletes and occur more frequently during physical activity or competition/practice, but there is growing evidence that device therapy is effective in athletes across a wide range of competitive sports. Failure of a device to convert a life-threatening arrhythmia, major injury from a shock, and increased lead failure have thus far not been reported in the prospective Implantable Cardioverter-Defibrillator Sports Registry, but follow-up remains relatively short. Thoughtful consideration of disease state, arrhythmia risk, and the potential dangers of device therapy during the desired sports is imperative before allowing participation. Frank discussion with children and families regarding the possibility of shocks during sports, as well as at other times, is imperative. Ongoing and future studies will help guide these decisions.